Phonon‐supported pseudospin phase transition in graphene. Issue 4 (15th December 2015) - Feng, Peng
Abstract : The phonon‐induced polarization of pseudospins in graphene is investigated in this work. On the basis of detailed quantum statistical calculations, it is found that the pseudospin average value always undergoes a sign change as the temperature is lowered through some critical value. This shows that the phonons not only induce a pseudospin polarization, but also lead to a phase transition of pseudospins. This phonon‐induced pseudospin polarization is somewhat like the photon‐induced polarization. If a circularly polarized light participates in pseudospin polarization besides the phonons, a refrigerating effect would occur.